Seasonal variation in the proximal determinants of undernutrition during the first 1000 days of life in rural South Asia: A comprehensive review - Madan, Emily M.; Haas, Jere D.; Menon, Purnima; Gillespie, Stuart (Elsevier, 2018)
In this review, the inﬂuence of seasonal variation on undernutrition during the ﬁrst 1000 days of life of life inrural South Asia is conceptualized using a modiﬁed framework developed under the “Tackling the Agricultureand Nutrition Disconnect in India” project. Evidence for the existence and extent of seasonality is summarizedfrom 14 studies reporting on six proximal determinants of undernutrition. A limited number of studies examineseasonal variation in risk factors for this age group. All available studies, however, report a compelling ﬁnding ofsigniﬁcant seasonal variation for at least one determinant of undernutrition. Research to clarify mechanisms forpotentially adverse eﬀects of seasonal variation on health and nutritional status during the ﬁrst 1000 days of lifeis needed